2022
DOI: 10.3390/ijms23020644
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue Uses in Peripheral Nerve Surgery

Abstract: Currently, many different techniques exist for the surgical repair of peripheral nerves. The degree of injury dictates the repair and, depending on the defect or injury of the peripheral nerve, plastic surgeons can perform nerve repairs, grafts, and transfers. All the previously listed techniques are routinely performed in human patients, but a novel addition to these peripheral nerve surgeries involves concomitant fat grafting to the repair site at the time of surgery. Fat grafting provides adipose-derived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Hydrogels may play a greater role in peripheral nerve crush injuries [ 83 ]. In addition, it should be pointed out that fat grafting has also become increasingly popular in peripheral nerve surgery in recent years [ 84 ], which is not contradictory to the operation in this study to reduce the fat content of ANXs by means of scCO2 extraction. On the one hand, the function of adipose tissue in fat grafting is mainly achieved by the adipose-derived stem cells (ADSCs) it contains, which can differentiate into many lineages and secrete neurotrophic and angiogenic factors [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 92%
“…Hydrogels may play a greater role in peripheral nerve crush injuries [ 83 ]. In addition, it should be pointed out that fat grafting has also become increasingly popular in peripheral nerve surgery in recent years [ 84 ], which is not contradictory to the operation in this study to reduce the fat content of ANXs by means of scCO2 extraction. On the one hand, the function of adipose tissue in fat grafting is mainly achieved by the adipose-derived stem cells (ADSCs) it contains, which can differentiate into many lineages and secrete neurotrophic and angiogenic factors [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we also attempted to restore systemic lipid metabolic homeostasis and investigated its rescue effect on neurogenesis [ 18 , 35 ]. As well known, AT not only served as an organ for energy storage but also as the endocrine organ to regulate metabolic homeostasis [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Standard reconstructive techniques use autograft for filling the gap between the proximal stump and the distal nerve in facial nerve reanimation[ 4 ]. Studies have shown that autograft use tend to be superior to acellular grafts in these cases, in which sensory nerves are considered as the gold standard graft for motor nerves reconstruction[ 8 ]. In designing our meta-analysis, we thus included only studies comparing autografts and stem cells for facial nerve reanimation in rats.…”
Section: Discussionmentioning
confidence: 99%